MEANING OF CONDITIONAL SENTENCE IN THE BURDAT OF KA'B BIN ZUHAIR AND IMAM AL-BUSIRI - Khalil Al-Hashemi, Ahad; Ahmad, Zeravan (Humanities Journal of University of Zakho, 2025)
The conditional style is one of the important styles of composition in the Arabic language, because this style contains tools that link two linguistic structures, the first is the conditional verb and the second is the answer to that condition. The meanings that these tools perform vary between those linguistic structures as a result of their diversity between nominal and literal, and in terms of work to decisive and non-decisive. This is what distinguishes the conditional style from other Arabic speech styles and gives it a distinct psychological impact on the soul of the addressee or listener. This effect differs in terms of urging to do the command, or urging to leave it. In this study, we examine the semantic function of conditional structures in the Burdah of Kaʿb ibn Zuhayr and that of Imam al-Busiri. We analyze and compare these structures in both poems, highlighting the similarities and differences in how conditional expressions are used to serve the poets' intended purposes. The analysis is based on a selection of poetic verses from the two Burdahs, through which we arrive at several findings that illustrate the differences in lexical choices and the semantic range of the conditional expressions, including meanings such as glorification, magnification, exaggeration, emphasis, diminution, prohibition, regret, and others. In addition to the theoretical side of what was mentioned from the old and modern studies of the conditional style, which are many studies due to the wide use of this style among the Arabs in ancient and modern times and its prevalence in their speech, so the research was based on the theoretical and applied study.